Not just any land : a personal and literary journey into the American grasslands - Price, John, 1966- (University of Nebraska Press, 2004)
Though he'd lived in Iowa all his life, the allure of the prairie had somehow eluded John Price-until, after a catastrophic flood, a brief glimpse of native wildlife suddenly brought his surroundings home to him. Not Just Any Land is a memoir of Price's rediscovery of his place in the American landscape and of his search for a new relationship to the life of the prairie-that once immense and beautiful wilderness of grass now so depleted and damaged as to test even the deepest faith.